2020
DOI: 10.1111/and.13943
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pharmacological mechanisms of Yinyanghuo as treatment of erectile dysfunction with network pharmacology‐based strategy

Abstract: The definition of erectile dysfunction (ED) encompasses the failure to develop or sustain an erection sufficient enough for sexual activity (Zhou, Chen, et al., 2019). It affects about 50% of men between the ages, 40 and 70, and thus regarded as a health problem of significance (Mitidieri et al., 2020). There are various causes related to ED, for example decrease of testosterone formation in the testis, decline of the amount and receptiveness of neurotransmitters and vasoactive amines, less vascular functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Furthermore, in vitro experiments have shown that ICA can inhibit the activity of PDE5 and increase the concentration of cGMP in the smooth muscle cells of the corpus cavernosum 9 . In addition, gene enrichment analysis suggested that ICA might affect penile erection by regulating 36 possible targets related to 10 signaling pathways 10 . Icariside II could improve erectile function in type 2 diabetes mellitus rats via the increased ratio of the smooth muscle cell to a collagen fibril, decreased mitochondrial autophagy by enhancing signaling via the phosphatidylinositol‐3‐kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway, advanced glycation end products level, receptor for advanced glycation end products, and oxidative stress 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in vitro experiments have shown that ICA can inhibit the activity of PDE5 and increase the concentration of cGMP in the smooth muscle cells of the corpus cavernosum 9 . In addition, gene enrichment analysis suggested that ICA might affect penile erection by regulating 36 possible targets related to 10 signaling pathways 10 . Icariside II could improve erectile function in type 2 diabetes mellitus rats via the increased ratio of the smooth muscle cell to a collagen fibril, decreased mitochondrial autophagy by enhancing signaling via the phosphatidylinositol‐3‐kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway, advanced glycation end products level, receptor for advanced glycation end products, and oxidative stress 11,12 .…”
Section: Introductionmentioning
confidence: 99%